Water, birth, the planet earth the land (Deerfield, Illinois Coronet MTI Film & Video, 1986)
Looks at how plants and animals emerged from the sea to thrive and develop on land and emphasizes the importance of the water cycle in this colonization. Focuses on how plants and animals adapted to their new environments and the new dangers they faced as they extended their ability to range freely over the land.
Distributed by International Book Center.
Grades 7 through adults.
Keywords: Evolution; Water -- Physiological effect; Hydrologic cycle; Adaptation (Biology)